PERLINDUNGAN HUKUM TERHADAP WISATAWAN DALAM PASOKAN JASA PARIWISATA OLEH BIRO PERJALANAN WISATA - Princess Innez Primantara (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
Purpose of this research is identify the construction norms about security and safety standard of tourist in the supply of tourism services by Tour Operator and the readiness Tour Operator in implementing tourists protection regulations in the supply of tourism services by Tour Operator. The research method used is a empirical legal research. Data and sources of data used are primary data, which derives from Tour Operator located around Denpasar and Badung, while secondary data used consisted of primary legal materials, secondary, and tertiary. Data collection techniques used are Study Documents Techniques and Interview Techniques, with the sampling technique used on the population is Non-Probability Sampling Techniques. The analysis used in this research is the Qualitative Data Analysis. As from April 11, 2014, the Government has set rules on Standards Service of Business Travel through Regulation of the Minister of Tourism and Creative Economy Number 4 of 2014. This allows for Tour Operator standardization problem as provided in the ministerial regulations, and constraints experienced by the Tour Operator to fulfill that standardization. In this regard, it is necessary to study more about the implementation of the protection of the law by a Tour Operator, after the ministerial regulation.